IMPLEMENTING SUSTAINABLE PRACTICES IN HEALTHCARE FACILITIES TO ENHANCE ENVIRONMENTAL HEALTH - Abdullah Hamd Al Hamdan, Sultan Saleh Alshaqawi, Mohammed Abdulrhman Mohammed Babaseel, Mohammed Habbas Mater Alshammari, Abdullatif Habbas Mater, Alshammari, Abdulaziz Muhammad Al-Mousa, ,; Abbasi Mufleh Muhammad AIRubaie,Dhafer Nasser, Rajeh Alghamdi, Yahya Mohammed Mohammed Maashi, Ibrahim Abdullah Nasser Mobarki, Mohammed Fahad M Alawni, Allami Essa Ahmed Wasili, (Chelonian Research Foundation, 2022)
The escalating climate crisis poses significant threats to healthcare systems worldwide, compromising their capacity to safeguard patients from climate-induced hazards. Healthcare facilities play a crucial role in addressing the impacts of climate change, but they may also contribute to the release of greenhouse gases during the provision of essential treatment and services. This study aims to evaluate current methods, identify barriers to implementation, and provide strategies for improvement to promote sustainable practices for enhanced environmental well-being in healthcare establishments. A quantitative research methodology was used, including the surveying of facility managers, healthcare professionals, and environmental health specialists from a sample of 100 healthcare companies. The findings revealed a positive perception of sustainability initiatives, with a general consensus on the significance of sustainability in the workplace. The analysis of questionnaire responses provided insights into workers' comprehension, commitment, and actions related to energy efficiency, water preservation, waste control, sustainable procurement, and staff education. This study contributes to the existing information by examining the connections between sustainable empowerment, green human resource management, and workers' green actions in the healthcare sector. The results underscore the importance of encouraging behaviors that prioritize sustainability, aligning organizational policies and procedures with sustainability goals, and providing enough training and support to employees. The findings provide valuable perspectives for healthcare institutions striving to enhance their ecological sustainability and contribute to the larger goal of providing healthcare coverage for everyone. Keywords: Healthcare facilities; sustainability; healthcare professionals; environmental health